From Judah Hadassi to Elijah Bashyatchi: studies in late medieval Karaite philosophy - Lasḳer, Daniʾel (The journal of Jewish thought and philosophy / Supplements, 2008)
Background -- Major thinkers -- Contacts with Rabbanite thinkers -- Topics -- Into the modern period